The Association between Standardized Serum 25-Hydroxyvitamin D Concentration and Risk of Anemia: A Population-Based Cross-Sectional Study - Yang Zhang; Xiaotong Wang; Jia Wang; Weiwei Hu; Xiaolu Song; Ding Yuan; Xianliang Yan (International Journal of Clinical Practice)
The relationship between standardized serum 25-hydroxyvitamin D (25(OH)D) concentration and incident anemia in the United States (U.S.) is unclear. The purpose of our study was to examine the association between serum 25(OH)D and anemia risk. We performed a cross-sectional analysis of the U.S. population participating in the National Health and Nutrition Examination Survey (NHANES) between 2001 and 2018. A generalized linear model and restricted cubic spline (RCS) plot curve were constructed to assess the relationship between serum 25(OH)D concentration and anemia incidence. Additionally, the association between serum 25(OH)D concentration and red blood cell (RBC) count and hemoglobin (HB) levels was investigated using generalized additive models with smooth functions. Subgroup analysis also was performed. A total of 29933 individuals were included in our research. After adjusting for known confounding variables, compared with the lowest quartile, the odds ratios (ORs) with 95% confidence intervals (CIs) for association of serum 25(OH)D with anemia across the second, third, and fourth quartiles were 0.735 (0.651, 0.829), 0.527 (0.461, 0.602), and 0.696 (0.611, 0.792), respectively. Serum 25(OH)D concentration was associated with anemia risk in a U-shaped pattern, as shown by an RCS plot (P for nonlinearity <0.001). In addition, RBC count and Hb levels initially increased and then decreased as serum 25(OH)D levels increased. Serum 25(OH)D concentration and risk of anemia are associated with a U-shaped curve in the U.S. general population. Serum 25(OH)D concentration in the range 59.7–70.3 nmol/l was associated with anemia incidence <1. Therefore, the risk of anemia can be reduced by close monitoring and appropriate vitamin D supplementation.